Strategi Optimalisasi Pendapatan Asli Daerah (Kasus Kota Cimahi) - Baban Sobandi (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2005)
Local government has responded the local autonomy policy, lauched by Central Government in 1999, with efforts for rissing original income. This effort can use negative impacts in both local economic activities and social welfares, due to incomplete prior anlysis of exixting condition and potency. This paper offers some alterbative strtaegies for original income optimalization. As an illustration, this paper use a case in the district of Cimahi in which the author found an acurate strategy for its original income optimalization such as data consilidation strategy and intensification startegy.